Students’ Writing Error in Descriptive Text: Study in the Seventh Grade Students of SMP Negeri 4 Arjosari Satu Atap - Hadi, Samsul; Hastuti, Eka Windri; Rahayu, Dwi (Jurnal Penelitian Pendidikan, 2023)
English, as an international language, played a crucial role in the world of education and global communication. In Indonesia, English is taught as a foreign language and is an integral part of the education curriculum. Writing in English is one of the essential components for developing students’ language skills, especially for students at the junior high school level. The purpose of this research was identified the writing errors made by students in descriptive texts. The study was conducted at SMPN 4 Satu Atap Arjosari Pacitan. This research used a quantitative research design. The data sources for this study were nine students from grade VII, selected through purposive sampling. The students’ descriptive text in writing test was used the primary data research. The research findings indicated that there were five aspects of errors in writing. The most dominant was language use, accounting 36%, contents 25%, vocabulary 18%, organizations 17%, mechanics 4%.